1989
DOI: 10.1017/s0272263100000619
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Retention of French by Dutch Students

Abstract: The present study investigated the retention of school-learned French language skills in Dutch students across a period of 4 years following the training period. Two training levels were investigated: 4 and 6 years of French training. The skills tested were all receptive: general receptive proficiency; listening and reading comprehension; and receptive phonological, lexical, and grammatical skills. In addition, selfassessment measures were administered.The results indicated that global skills improved, if anyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 10 publications
3
36
0
Order By: Relevance
“…Previous research on FL attrition includes works by Cohen (1989), Gardner (1985, Nakuma (1997), Starren (1998), Weltens, van Els andSchils (1989), Weltens and Grendel (1993).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on FL attrition includes works by Cohen (1989), Gardner (1985, Nakuma (1997), Starren (1998), Weltens, van Els andSchils (1989), Weltens and Grendel (1993).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding maintenance classes in private institutes, Yashiro (1992) indicated that these classes help returnees to maintain their foreign language; however, the returnees feel free in building communication with foreign students. In a similar study, which aimed at exploring longterm retention of French by Dutch students, Weltens, Van Els, and Schils (1989) observed an increase in proficiency, despite the fact that subjects had very low contact with French in the intervening years. They related this increase in proficiency to "general cognitive maturation, further academic training, and continued learning of other foreign languages" (Weltens, Van Els, & Schils, 1989, p. 214).…”
Section: Exploring Efl Learners' Experience Of Foreign Language Profimentioning
confidence: 96%
“…Some scholars explored the evidence of attrition phenomenon in different parts of language knowledge (Berman & Olshtain, 2015;Tomiyama, 2000). On the other hand, others focused on factors and techniques that contribute to language proficiency development (Arevalo, 2010;Bahrick, 1984;Garza, 1991;Huang & Eskey, 2000;Markham, 1999;Rott, 1999;Schneider, Healy, & Bourne, 2002;Snow, Padilia, & Campbell, 1988;Valmori, 2014;Weltens, Van Els, & Schils, 1989;Yashiro, 1992). None of these studies, however, explored and theorized EFL learners' experience of proficiency maintenance.…”
Section: Exploring Efl Learners' Experience Of Foreign Language Profimentioning
confidence: 99%
“…It is particularly worth mentioning that under the guidance of these theories, lexical attrition study yielded many fruits ranged from early introspective study to later series of quantitative analysis study. Some researchers concentrated on the differences of attrition in lexical and other language system, such as Anderden(1982), Bahrick(1984), Mooncraft & Gardner (1987), Weltens (1989), Altenberg (1991), Weltens & Grendel (1993) …”
Section: A Foreign Language Attrition Researchmentioning
confidence: 99%